Development of Volleyball Bottom Passing Model - Fery Ariyanto; Firmansyah Dlis; Moch Asmawi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This research aims to develop volleyball bottom passing exercises. Based on observations made in elementary schools in Jambi, there is still a low ability of basic volleyball passing techniques, so it is necessary to develop the form of exercise. This development uses the R&D model with the Borg and Gall model. While the data analysis technique uses effectiveness tests and gain scores. The results of the development of volleyball bottom passing training equipment meet the criteria that are quite valid for expert experts and are in the Very Meet or Decent category. The conclusion of this study is that the development of a volleyball bottom passing exercise model is very feasible to be used as a training model for basic bottom passing techniques in volleyball games